2004
DOI: 10.1002/ar.a.20075
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy of the killer whale (Orcinus orca) from magnetic resonance images

Abstract: This article presents the first series of MRI-based anatomically labeled sectioned images of the brain of the killer whale (Orcinus orca). Magnetic resonance images of the brain of an adult killer whale were acquired in the coronal and axial planes. The gross morphology of the killer whale brain is comparable in some respects to that of other odontocete brains, including the unusual spatial arrangement of midbrain structures. There are also intriguing differences. Cerebral hemispheres appear extremely convolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
4
29
1
Order By: Relevance
“…Structures of the basal ganglia (such as the caudate nucleus and the putamen) were recognized (Figures 5B,6B,12B,and 13B). Unlike previous reports of odontocete MRI studies of formalin-fixed brains (Marino et al, 2001a;Marino et al, 2001c;Marino et al, 2004a;Marino et al, 2004b;Marino et al, 2003a;Marino et al, 2003b;Marino et al, 2001c), the hippocampus was located and was found to be quite small relative to the overall size of the brain ( Figures 7B, 8B, and 15B). This observation was similar to the findings on the bottlenose dolphin hippocampus observed by Jacobs et al (1979).…”
Section: Three-dimensional Reconstructions and Neuroanatomy Of The Sucontrasting
confidence: 97%
See 2 more Smart Citations
“…Structures of the basal ganglia (such as the caudate nucleus and the putamen) were recognized (Figures 5B,6B,12B,and 13B). Unlike previous reports of odontocete MRI studies of formalin-fixed brains (Marino et al, 2001a;Marino et al, 2001c;Marino et al, 2004a;Marino et al, 2004b;Marino et al, 2003a;Marino et al, 2003b;Marino et al, 2001c), the hippocampus was located and was found to be quite small relative to the overall size of the brain ( Figures 7B, 8B, and 15B). This observation was similar to the findings on the bottlenose dolphin hippocampus observed by Jacobs et al (1979).…”
Section: Three-dimensional Reconstructions and Neuroanatomy Of The Sucontrasting
confidence: 97%
“…Two-dimensional magnetic resonance images of the subadult (CCSN05-084-La) also revealed distinguishing features of odontocete brains, as previously observed in other MRI studies of formalin-fixed toothed whale brains (Marino et al, 2001a;Marino et al, 2004a;Marino et al, 2004b;Marino et al, 2003a;Marino et al, 2003b;Marino et al, 2001c) (Figures 4-19). Telencephalon.…”
Section: Three-dimensional Reconstructions and Neuroanatomy Of The Susupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, the gyrification indices for these two odontocete species, 2.4 and 2.7, respectively, substantially exceed that of modern humans. Furthermore, a qualitative description of the killer whale (Orcinus orca) brain suggests a neocortical gyrification index even higher than in Tursiops and Delphinus (Marino et al, 2004b).…”
Section: Neuroanatomical Evidencementioning
confidence: 98%
“…The reduction of the hippocampus and related structures in odontocetes is particularly striking in light of the fact that odontocetes possess robust memory and learning skills (Mercado et al, 1998(Mercado et al, , 1999 which, in other mammals, depend highly on the hippocampus. An interesting possibility is that some learning and memory functions were transferred from the reduced hippocampal formation to the extremely well-developed cortical limbic lobe (periarchicortical field above the corpus callosum and the entorhinal cortex) in odontocetes (Oelschlager and Oelschlager, 2002;Marino et al, 2003Marino et al, , 2004b. This hypothesis would account for the copious behavioral evidence for strong learning and memory skills in odontocetes (Herman, 2006).…”
Section: Reduction Of Olfaction and Reproportioning Of The Limbic Systemmentioning
confidence: 99%